Correlation studies of sunflower Alternaria leaf blight with weather parameters: Correlation studies of sunflower Alternaria leaf blight with weather parameters - K VENKATA RAMANAMMA,; S NEELIMA,; K PRABHAKAR, (Journal of Oilseeds Research, 2020)
To assess the impact of weather conditions on the progress of Alternaria leaf blight in two cultivars KBHS-44and Morden of sunflower, an experiment was conducted during kharif 2013-14 and 2014-15. It was recorded that per cent disease index (PDI) was positively correlated with relative humidity during morning (RH1), relative humidity during evening (RH2), and with crop age for two cultivars. These correlations were found to be significant under protected and unprotected conditions. PDI was negatively correlated with temperature maximum significantly and also with rainy days, sunshine hours and wind velocity. But the effect of temperature minimum was not significant.